International Multicenter Study on the Impact of Extracapsular Lymph Node Involvement in Primary Surgery Adenocarcinoma of the Esophagus on Overall Survival and Staging Systems. Issue 5 (November 2015) - Nafteux, Philippe R.; Lerut, Antoon M.; Moons, Johnny; Hölscher, Arnulf H.; Bollschweiler, Elfriede; Henegouwen, Mark I. van Berge; Lagarde, Sjoerd M.; van Lanschot, Jan J.; Messager, Mathieu; Mariette, Christophe; D'Journo, Xavier B.; Thomas, Pascal A.; et al.
Abstract : Objective: The current pathological lymph node (pN) staging is based on the number of positive lymph nodes but does not take into consideration characteristics of the involved lymph nodes itself. The current study aims to examine the prognostic value of extracapsular lymph node involvement (EC-LNI) and intracapsular lymph node involvement (IC-LNI) for esophageal adenocarcinoma treated by primary surgery. Methods: From the databases of five European high volume centers, 1639 adenocarcinoma patients with primary R0-resection were withheld after excluding 90-day mortality. Oncologic variables, including number of resected lymph nodes, number of resected positive lymph nodes, and EC-LNI/IC-LNI were examined. The Union Internationale contre le Cancer (UICC) 7th edition prognostic staging was used as baseline staging system. Statistical analysis was performed by Cox proportional hazards modeling and verified using the Random Survival Forest technique. Results: EC-LNI showed significantly worse overall 5-year survival compared with IC-LNI overall (13.4% vs 37.2%, P < 0.0001), including in each pN-catergory [16.4% vs 45.6% in pN1 ( P < 0.0001), 16.1% vs 23.8% ( P = 0.047) in pN2 ( P = 0.065), and 8.7% vs 26.3% in pN3 categories, respectively]. pN1 IC-LNI patients show a 5-year overall survival comparable ( P = 0.92) with stage IIB (ie, pT3N0). Reclassifying the UICC prognostic stages according to these findings into an adapted staging model showed a significant ( P < 0.0001) increase in homogeneity, discriminatory ability, and monotonicity compared with the original UICC TNM 7th edition prognostic staging. Conclusions: These data suggest that lymph node capsular status is an important prognostic factor and should be considered for the future edition of the TNM staging system for esophageal cancer.